Identifying High Frequency Peakers using the Korean VLBI Network. Issue 1 (February 2016) - Jeong, Y.; Sohn, B. W.; Chung, A.; Park, S.; Park, P.
Abstract: High Frequency Peakers (HFPs) are known to be promising targets to study the AGN properties at their very early evolutionary stage. To date, HFP classification has been usually relied on the spectral shape with the relatively sparse or short time range monitoring. However, HFP samples are often contaminated by blazars which are compact and highly variable, and hence may behave in similar ways to HFPs. In this work, we challenge to identify genuine young AGNs by long‐term monitoring of HFP candidates at high radio frequencies. We performed single‐dish monitoring of 19 candidates in 18 epochs over 2.5 years at 22 and 43 GHz simultaneously, using the Korean VLBI Network (KVN). Also, using the KVN and VERA array (KaVA), we carried out 22 and 43 GHz VLBI observations of seven candidates from our sample, and investigated their parsec‐scale (milli‐arcsecond scale) morphology. We discuss the results of the source classification from our long‐term single dish monitoring observation and the preliminary results of follow‐up VLBI observation. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)